Boron nitride modified reduced graphene oxide as solid‐phase microextraction coating material for the extraction of seven polycyclic aromatic hydrocarbons from water and soil samples. Issue 7 (10th February 2021) - Li, Hongda; Hou, Baoxiu; Wang, Ling; Zang, Xiaohuan; Wang, Chun; Wang, Zhi
Abstract: A novel hexagonal boron nitride modified reduced graphene oxide material was synthesized and used as the adsorbent for the solid‐phase microextraction of seven polycyclic aromatic hydrocarbons from water and soil samples prior to their detection by gas chromatography‐flame ionization detector. Under optimal conditions, the linear response range of the analytes for water sample is 0.25–50 ng/mL with the correlation coefficients ( r ) ranging between 0.9953 and 0.9996. The linear range for soil sample is 1.0–400 ng/g with r ranging from 0.9959 to 0.9999. On the basis of the signal‐to‐noise ratio of 3, the limits of detections for the analytes ranged from 0.05 to 0.15 ng/mL for water samples, and from 0.3 to 0.5 ng/g for soil samples. The relative recoveries of the seven polycyclic aromatic hydrocarbons for water and soil samples were in the range of 79.55–120.0 and 78.76–120.8%, respectively. The relative standard deviations for the determination of the analytes in water and soil samples were lower than 11 and 10%, respectively. The method is simple and suitable for the determination of polycyclic aromatic hydrocarbon residues in water and soil samples.